The Polish Interwar Period in the Mirror of Collective Reception - Daradanova, Elena (Poznańskie Studia Slawistyczne, 2020)
The subject of this review is the reception of Polish interwar literature in Bulgaria, and particularly the anthology Polish Poetry between the Two World Wars (2019), by Panayot Karagyozov and the special issue of Literaturen vestnik (2018), devoted to Polish culture from that period. The focus of the review is on the simultaneous reception of both translated poetry and literarycritical articles.